Effect of the teak-sunn hemp association on fertility of an Eutric Gleysol and weed community - Maza- Landero, Mariela Guadalupe; García-López, Eustolia; Obrador-Olán, José Jesús; Castelán- Estrada, Mepivoseth; Carrillo-Ávila, Eugenio; Juárez-López, José Francisco (Ecosistemas y Recursos Agropecuarios, 2023)
The effect of the teak-crotalaria association on soil fertility, early stage teak growth and nutrition, and the weed community was evaluated. In recent decades, teak wood has increased its value due to its hardness and durability, causing increases in the cultivated area in Mexico, where the use of legumes as green manures is emerging as a technology that contributes to the sustainability of the ecosystem and the reduction of environmental damage, associated with the use of chemical fertilizers. The research was carried out from August-2020 to January-2021 in Town C34 "Benito Juárez", Huimanguillo, Tabasco, Mexico. Soil fertility was evaluated by sampling and physical-chemical analysis at the beginning and end of the investigation. Crotalaria yield was evaluated 60 days after germination. The teak-crotalaria association did not influence the parameters of the soil studied, with the exception of Ni, which showed significant differences between treatments. No differences were observed in the height and diameter of the theca between treatments, nor in the concentration of N, P, K, Ca and Mg at six months, although the nutritional contents were at sufficiency levels. As a result of the five samples of weeds, a floristic list was obtained comprising 24 species, 20 genera and 13 families, highlighting Fabaceae and Poaceae. Richness (S) and diversity (H’) had low values, slightly higher where there was no AV, the highest corresponded to 30 dd after incorporating the crotalaria. The most important species was the star grass; followed by humidicolous grass, the golden button, the chibolita and L. crustacea.
Keywords: Green manure (GM); nutrimental concentration; nutrient; diversity; importance value index (IVI)